2021
DOI: 10.1128/mra.00443-21
|View full text |Cite
|
Sign up to set email alerts
|

Full Genome Sequence of a Methanomassiliicoccales Representative Enriched from Peat Soil

Abstract: The full genome of a Methanomassiliicoccales strain, U3.2.1, was obtained from enrichment cultures of percolation fen peat soil under methanogenic conditions, with methanol and hydrogen as the electron acceptor and donor, respectively. Metagenomic assembly of combined long-read and short-read sequences resulted in a 1.51-Mbp circular genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Hence, we formally propose the new genus Methanomethylophilus as the type genus for the new family Methanomethylophilaceae , with the new species Methanomethylophilus alvi as the type species (see section “Taxonomy”). We also propose to include the new genera Methanarcanum , Methanogranum , Methanoplasma , and Methanoprimaticola in this family to accommodate other highly enriched cultures with sequenced genomes that so far have only Candidatus status ( Iino et al, 2013 ; Lang et al, 2015 ; Weil et al, 2021 ; Chibani et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we formally propose the new genus Methanomethylophilus as the type genus for the new family Methanomethylophilaceae , with the new species Methanomethylophilus alvi as the type species (see section “Taxonomy”). We also propose to include the new genera Methanarcanum , Methanogranum , Methanoplasma , and Methanoprimaticola in this family to accommodate other highly enriched cultures with sequenced genomes that so far have only Candidatus status ( Iino et al, 2013 ; Lang et al, 2015 ; Weil et al, 2021 ; Chibani et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic and metataxonomic studies have revealed the global environmental distribution of Methanomassiliicoccales representatives [4,7,52,53] and a particular association with the gut microbiomes of animals [3,4,19], including ruminants [54,55] and humans [5,6,56]. Over the last 10 years, multiple enrichment cultures of Methanomassiliicoccales have been described [1,4,7,9,10,13,14,17,18], although only one generalist member (M. luminyensis B10 T ) of this order has been obtained in axenic culture and described so far [2]. Here, we report the description of a second hydrogenotrophic methyl-reducing methanogen representative of this order (strain Mx-05 T ), being the first isolate of a familylevel clade associated with the gut microbiome of various animals.…”
Section: Discussionmentioning
confidence: 99%
“…A closely related species, 'Candidatus Methanomassiliicoccus intestinalis', was enriched from a human fecal sample [9] and is more prevalent in human populations than M. luminyensis [5,6]. Two additional enrichment cultures of Methanomassiliicoccaceae were generated from freshwater sediment [7] and peat soil [10]. A second family-level lineage within the Methanomassiliicoccales family was retrieved primarily from samples of the gut environment.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] illustrates two fundamental principles about our connection to microbes: 1) We are intimately connected to Earth's microbes, 2) Even if much of our microbiome has some stability, we are constantly exchanging microbes, microbial genes, physiologically-modifying chemicals, and gathering information from and sharing information with the microbes beyond our body. The human body is open to the environment.…”
Section: Connecting To the Iom Via Meditation Embodied Cognition And ...mentioning
confidence: 99%
“…An examination of ancient archaea and extremeophile bacteria reflected in Table 4 shows that we embody not only our ancestral history but also that of life on Earth. In the Table 's first example, an archaean representative of Methanomassiliicoccales (designated as strain U3.2.1) was isolated via an enrichment culture from a Northern Germany peat soil and was shown to have a sequence identity with the 16S rRNA gene of human gut-isolated Methanomassiliicoccus luminyensis 10B of 88.6% [123]. Methanogenesis is an important process of life on Earth and can be significant in specialized ecological niches within our body.…”
Section: Copyright© Rodney R Dietertmentioning
confidence: 99%